2012
DOI: 10.1186/1742-2094-9-99
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention with a small molecule inhibitor for tumor nefosis factor-α prevents cognitive deficits in a triple transgenic mouse model of Alzheimer’s disease

Abstract: BackgroundChronic neuroinflammation is an important component of Alzheimer’s disease and could contribute to neuronal dysfunction, injury and loss that lead to disease progression. Multiple clinical studies implicate tumor necrosis factor-α as an inflammatory mediator of neurodegeneration in patients with Alzheimer’s because of elevated levels of this cytokine in the cerebrospinal fluid, hippocampus and cortex. Current Alzheimer’s disease interventions are symptomatic treatments with limited efficacy that do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 79 publications
4
78
0
Order By: Relevance
“…These findings support the results of Gabbita et al [28] who found that 3xTg-AD mice had significant working memory deficits in the radial arm maze. They also support the findings that 3xTg-AD mice have reference memory deficits in the MWM [20,[29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings support the results of Gabbita et al [28] who found that 3xTg-AD mice had significant working memory deficits in the radial arm maze. They also support the findings that 3xTg-AD mice have reference memory deficits in the MWM [20,[29][30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 93%
“…To date, only one study has examined working and reference memory of 3xTg-AD mice. Using the win-shift paradigm in the radial arm maze, Gabbita et al [28] found that 6-month old 3xTg-AD mice made significantly more working memory errors than B6129SF2/J controls, but did not differ in number of reference memory errors. Most studies investigating spatial reference memory in the 3xTg-AD mice using the Morris water maze (MWM) found no reference memory deficits at 2 months of age [29][30][31][32][33], although Stover et al [34] reported learning deficits in 3xTg -AD mice in the MWM at 2 months of age.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, we found that both T and 3,6′-DT reduced brain damage and improved functional outcome when administered prior to MCAO/R, but only 3,6′-DT was effective when treatment was delayed for 3 hr after the stroke. This differential efficacy of T and 3,6′-DT with delayed treatment may be the result of the different abilities to enter and be retained within the brain, in line with the ability of 3,6′-DT but not T to lower brain TNF levels and improve cognition in an animal model of Alzheimer’s disease (Gabbita et al, 2012). …”
Section: Discussionmentioning
confidence: 87%
“…Inhibition of TNFa activity ameliorated AD-like pathology and cognitive impairment in AD animal models. Thalidomide, a TNFa inhibitor, significantly attenuated neuroinflammation, Ab deposition, and tau phosphorylation ) and improved memory function (Gabbita et al 2012). Infliximab, the antibody against TNFa, reduced the levels of TNFa, amyloid plaques, and tau phosphorylation in transgenic mice (Shi et al 2011a).…”
Section: Agents That Inhibit Tnfa Activitymentioning
confidence: 97%